2006
DOI: 10.1016/s0022-5347(05)00160-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Death Receptors in Bladder, Prostate and Renal Cancer

Abstract: Research into the death receptor pathways has demonstrated the key role that pathway aberrations have in the initiation and progression of malignancies of the bladder, prostate and kidney. This new understanding has resulted in exciting approaches to restore the functionality of these pathways as a novel therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…Caspases are critical protease mediators of apoptosis triggered by different stimuli including TRAIL (9,34,35). In the present study, we found that in T24 and 253j cells treated with the combination of mapatumumab and EPI, the initiative caspases such as caspase-8, -9 and effective caspases including caspase-3 were significantly activated.…”
Section: Discussionsupporting
confidence: 51%
“…Caspases are critical protease mediators of apoptosis triggered by different stimuli including TRAIL (9,34,35). In the present study, we found that in T24 and 253j cells treated with the combination of mapatumumab and EPI, the initiative caspases such as caspase-8, -9 and effective caspases including caspase-3 were significantly activated.…”
Section: Discussionsupporting
confidence: 51%
“…Korkolopoulou and colleagues reported that expression of FLIP in bladder cancer has been associated with advanced stage and grade (24). Therefore, it is expected that FLIP might be as an indicator of prognosis (25). Several studies have also shown that HDAC inhibitors can reduce the expression of FLIP (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to rTRAIL-induced apoptosis was reported in cell lines derived from human colon, lung, breast, kidney, brain and skin cancer (Ashkenazi et al, 1999). Till date, effective apoptosis induction by rTRAIL has been reported in human melanoma, leukemia, multiple myeloma, breast, bladder, prostate, renal or colon cancer in single treatments and/or combination therapy with chemotherapeutic agents (Chawla-Sarkar et al, 2002;An et al, 2003;Buchsbaum et al, 2003;van Geelen et al, 2003;VoelkelJohnson, 2003;Merchant et al, 2004;Georgakis et al, 2005;Kaufmann and Steensma, 2005;Kurbanov et al, 2005;Pukac et al, 2005;Bucur et al, 2006;Marini et al, 2006;O'Kane et al, 2006;Zeng et al, 2006). Thus, these cancers are the most promising indications for clinical trials of TRAIL and anti-DR5/DR4 mAb.…”
Section: Clinical Applicationmentioning
confidence: 99%